Bilirubin Oxidation Products and Cerebral Vasoconstriction - Robert M. Rapoport (Frontiers Media S.A., 2018)
Key evidence in support of the hypothesis that bilirubin oxidation products (BOXes) contribute to the vasoconstriction associated with subarachnoid hemorrhage (SAH) are the (1) presence of BOXes in cerebral spinal fluid from SAH patients and (2) ability of one or more BOXes to elicit vasoconstriction. We critically evaluate this key evidence, detail where gaps remain, and describe recent approaches that will address these gaps.